2010
DOI: 10.1002/cphc.201000715
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Measures for Vectors, Matrices, Operators and Functions

Abstract: We introduce the general form of the continuous chirality measure (CCM), which is a quantitative estimation of the degree of chirality for a given object. The generalization makes it possible to calculate the chirality content of any mathematical description of a system by vectors, matrices, operators and functions. Another advantage of the new methodology is the ability to provide analytical expressions for the chirality measures. We apply it for specific cases, including vectors and molecules (amino acids), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 137 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Quantification of Chirality. We have previously shown that introducing an absolute, rather than a relative to a reference 81 (such as the Hausdorff chirality measure 82,83 ), pseudoscalar chirality indicator derived from the geometry of a chiral molecule 67,84,85 or a nanoscale particle 86,87 decorated with chiral molecules gives values for a chirality index, G oa a , that matches extraordinarily well with the experimental data and trends of the calculated values for HTP. In particular, G oa a allowed us to make comparisons and predictions and draw conclusions about the chiral induction potential of chiral organic molecules as well as GNRs and polyhedral (quasispherical) Au NPs decorated with these exact chiral molecules.…”
supporting
confidence: 60%
“…Quantification of Chirality. We have previously shown that introducing an absolute, rather than a relative to a reference 81 (such as the Hausdorff chirality measure 82,83 ), pseudoscalar chirality indicator derived from the geometry of a chiral molecule 67,84,85 or a nanoscale particle 86,87 decorated with chiral molecules gives values for a chirality index, G oa a , that matches extraordinarily well with the experimental data and trends of the calculated values for HTP. In particular, G oa a allowed us to make comparisons and predictions and draw conclusions about the chiral induction potential of chiral organic molecules as well as GNRs and polyhedral (quasispherical) Au NPs decorated with these exact chiral molecules.…”
supporting
confidence: 60%
“…A number of different metrics have been proposed in the literature attempting to quantify the chirality of a molecule or a certain object. Some of these are based on the distance between a given structure and the closest achiral structure 39 or on the Hausdorff distance between the sets of points representing two specular images 40 . Here we employ another approach that introduces an absolute, rather than relative to a reference, pseudoscalar indicator derived from the molecule (or more generally object) geometry 41 43 .…”
Section: Resultsmentioning
confidence: 99%
“…The factor 100 expands the scale for convenience, so that the value of the measure ranges from zero to an upper bound which is lower than 100 (the 100 limit is obtained in the more general Continuous Symmetry Measure). For a more detailed description of the CCM computational methods see refs for examples of its applications across chemistry see refs …”
Section: The Studied Clusters and The Quantitative Computational Methodsmentioning
confidence: 99%